Optimalisasi Pemanfaatan Platform Pembelajaran untuk Meningkatkan Pengelolaan Kelas yang Baik Dimasa Pandemi - Fatimah, Siti (Prosiding University Research Colloquium, 2021)
This study aims to see the extent of the use of learning platforms and the impact of usingvarious learning platforms. The research method used a survey method with the subjectbeing the teacher of SD Negeri Purwosari, Secang District. Based on the results of thestudy, the use of the learning platform is still not optimal and causes several obstaclesduring online learning. These obstacles come from both teachers, parents and students.Teachers who lack innovation and only use the Whatsapp and Youtube platforms, studentswho have difficulty understanding the material, teachers who have difficulty evaluatingor assessing learning, and parents who complain a lot about online learning. Based on theresearch results, optimizing the use of online learning platforms is able to improve goodclassroom management during the pandemic.